Ambient Air‐Processed Wide‐Bandgap Perovskite Solar Cells with Well‐Controlled Film Morphology for Four‐Terminal Tandem Application. Issue 8 (24th May 2022) - Jang, Gyeong Sun; Kim, Youngwoong; Kim, Young Yun; Yoo, Jason J.; Kim, Geunjin; Jeon, Nam Joong; Lee, Hae-Seok; Kim, Donghwan; Seo, Jangwon
Abstract : Perovskite solar cells (PSCs) have emerged as the next generation of solar cells because of the promising nature of creating tandem solar cells with Si photovoltaics. Wide‐bandgap PSCs are developed to improve the power conversion efficiency (PCE) and stability of tandem devices. For the mass production of tandem solar cells, not only is a limitation of scalable coating a critical factor, but uncontrollable grain growth in ambient air impedes commercialization. Serious differences in morphology depending on the experimental environment are found. In the ambient air processing system, severe wrinkles and voids resulting in deteriorated photovoltaic performance are found as compared with those in N2 condition. It is suggested that humidity in the air plays a crucial role in the remaining perovskite intermediate phase and the rate of solvent evaporation during the spin‐coating procedure. Herein, void‐ and wrinkle‐free perovskite films using methyl ammonium chloride and formamide are fabricated, thus leading to efficient PSCs with a PCE of 20.6%. Furthermore, newly designed perovskite films to blade coating for large‐area fabrication as well as to semitransparent PSCs for a four‐terminal silicon/perovskite tandem solar cell with a PCE of 25.2% are applied. Abstract : Methylammonium chloride and formamide as additives are developed for highly efficient and reproducible wide‐bandgap perovskite solar cells in ambient air processing. Due to overcoming drawbacks resulting from processing at ambient air via additives, perovskite solar cells with well‐controlled film morphology and passivation exhibit superior photostability and improved power conversion efficiency compared with the pristine film.